KERJASAMA INDONESIA DAN SEAMOLEC DALAM BIDANG PENDIDIKAN TERBUKA DAN JARAK JAUH TAHUN 2015-2019 - Anindita Winandha, (2021)
The unequal access to education and its non-optimal implementation will affect the quality of Indonesia's human resources. As time goes by, science and technology are developing rapidly to impact aspects of education. In this regard, the Ministry of Education and Culture has prepared a Strategic Plan based on Presidential Regulation No. 5 of 2010 concerning the 2015-2019 National Medium-Term Development Plan (RPJMN), which collaborates with SEAMOLEC as their working unit. SEAMOLEC is an institution under the auspices of SEAMEO that focuses on developing Open and Distance Education (PTJJ) by utilizing ICT. This research was conducted to examine the implementation of the collaboration between Indonesia and SEAMOLEC in Open and Distance Education (PTJJ) to improve the quality of education in Indonesia and its human resources. This research was conducted using the theory of international cooperation to analyze the cooperation between Indonesia and SEAMOLEC with SEAMEO member countries, the concept of a regional organization to explain the institutions of SEAMEO SEAMOLEC, and the concept of national interest to find out the cooperation carried out by Indonesia and SEAMOLEC can achieve interests. Indonesia in education issues. The results of the research carried out can be seen from the programs designed in collaboration between Indonesia and SEAMEO SEAMOLEC 2015-2019, such as online training, School/University Partnership, PTJJ in West Java, and the Common ASEAN Tourism Curriculum (CATC) showing an increase in the quality of education and human resources in Indonesia. Keywords: international cooperation, Indonesia, SEAMOLEC, open and distance education